Thermal interface materials with sufficiently vertically aligned and interconnected nickel-coated carbon fibers under high filling loads made via preset-magnetic-field method. (8th September 2021) - Zhang, Xinfeng; Zhou, Shuling; Xie, Bin; Lan, Wei; Fan, Yiwen; Hu, Run; Luo, Xiaobing
Abstract: Efficient thermal dissipation has become a critical factor limiting the development of electronic devices. Thermal interface materials (TIMs) connecting the surfaces of heat source and heat sink, are important to guarantee stable and sufficient heat dissipation from heat source to heat sink. Carbon fibers (CFs) are widely used as the reinforcing fillers to enhance the thermal conductivities of polymer-based composites because of their extremely high thermal conductivities in axial direction. However, conventional methods of CFs cannot take full advantage of their high thermal conductivities because heat conductive channels in composite are not efficiently built due to the greatly larger viscosity of composite caused by CFs under high filler concentration. To solve this problem, we report a magnetic field-based and viscosity-independent method to fabricate the nickel-coated carbon fibers (NICFs) filled polydimethylsiloxane (PDMS) composites with the highspeed through-plane heat conductive channels under high filler concentration. The NICFs-composite shows 69 times enhanced through-plane thermal conductivity (10.50 W/(m∙K)) compared to that of pure PDMS (0.15 W/(m∙K)) and low thermal expansion coefficient (CTE) of 55.14 ppm/°C at 51.54 wt%. Compared to commercial TIMs, the NICFs-composites exhibits better thermal performance, demonstrating potential application prospects in electronic devices cooling area. Graphical abstract: Image 1